1995
DOI: 10.1002/ffj.2730100307
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to the scent of cacti

Abstract: The family of Cactaceae consists of around 1500 species in about 100 genera, being mostly leafless trees or shrubs of succulent appearance and often having attractive flowers. In comparison to other families, e.g. Orchidaceae, the flowers of Cactaceae are of a morphologically primitive structure. Nevertheless, they show adaptive traits towards different groups of pollinators. Adaptations are reflected to a certain degree also in their scent composition as illustrated by the selection of analytical data present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 16 publications
3
79
0
4
Order By: Relevance
“…Alternatively, the compound may be effective for attraction of small mammals because it is indicative of certain foods. Interestingly, although 3-hexanone is not a component of most floral scents [3], it occurs in the scents of a variety of neotropical bat-pollinated species, including as a major component of members of the Bromeliaceae and Bignoniaceae [12] and as a minor component of members of the Amaryllidaceae [12] and Cactaceae [33].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the compound may be effective for attraction of small mammals because it is indicative of certain foods. Interestingly, although 3-hexanone is not a component of most floral scents [3], it occurs in the scents of a variety of neotropical bat-pollinated species, including as a major component of members of the Bromeliaceae and Bignoniaceae [12] and as a minor component of members of the Amaryllidaceae [12] and Cactaceae [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work on the coevolving interactions between woodland star plants (Saxifragaceae: Lithophragma) and their pollinating floral parasites in the Greya moth genus (Prodoxidae) has shown that these closely related plants have an extraordinarily diverse set of floral scents that vary markedly among species and even subspecies , at levels comparable to differences between genera in other studies (e.g., Kaiser and Tollsten 1995;Levin et al 2001). The production of such a diverse array of compounds is likely to incur energetic (Gershenzon 1994;Wright and Schiestl 2009) and ecological costs, because the same compounds that attract mutualistic insects also may attract antagonistic herbivores and seed predators (Irwin et al 2004;Proffit et al 2007;Schiestl et al 2011;Theis 2006;Theis and Adler 2012;Wright and Schiestl 2009).…”
Section: Introductionmentioning
confidence: 86%
“…Solvent samples (E. bicolor S1 and E. humilis S1, see electronic supplementary material, table S2, for sampling details) were analysed by Dr Roman Kaiser (Givaudan, Switzerland) using methods described in Kaiser & Tollsten (1995). Thermal desorption samples (five for each species; see electronic supplementary material, table S2, for sampling details) were analysed on a Varian CP-3800 GC (Varian, Palo Alto, CA, USA) coupled to a Varian 1200 quadrupole mass spectrometer with a Varian 1079 injector equipped with a 'ChromatoProbe' thermal desorbtion device using methods described in Shuttleworth & Johnson (2009a).…”
Section: Methodsmentioning
confidence: 99%